The core musculature in male prepubescent tennis players and untrained counterparts: a volumetric MRI study - Sanchis-Moysi, J.; Idoate, F.; Álamo-Arce, D.; Calbet, J. A. L.; Dorado, C. (Journal of Sports Sciences, 2017)
The effects of exercise on the core musculature have not been investigated in prepubescents. The main purpose of the present study was to determine the volume and degree of asymmetry of rectus abdominis, obliques and transversus abdominis, quadratus lumborum, iliopsoas, gluteus and paravertebralis muscles in prepubescent tennis players and in untrained boys. The muscle volume was determined using magnetic resonance imaging (MRI) in 7 male prepubescent tennis players and 10 untrained controls (mean age 11.0 ± 0.8 years, Tanner 1-2). After accounting for height and body weight as covariates, the tennis players had 14-34% greater volume than the controls in all the muscles analysed (P < 0.05) except in paravertebralis, dominant quadratus lumborum and non-dominant gluteus, which had similar volumes in both groups (P = NS). Compared to controls, the tennis players displayed a greater degree of asymmetry in quadratus lumborum and rectus abdominis (3% vs. 15%, P < 0.01 and 8% vs. 17%, P = 0.06, respectively). The level of asymmetry of obliques and transversus abdominis, iliopsoas, gluteus and paravertebralis muscles was similar in both groups (P = NS). In conclusion, tennis playing at prepubertal ages induces a selective hypertrophy of the core musculature and exaggerates the degree of asymmetry of quadratus lumborum and rectus abdominis compared to untrained boys.